Association Between Inflammation and Appetite in Healthy Community-Dwelling Older Adults-An enable Study. - Chareh, Neshat; Kiesswetter, Eva; Kob, Robert; Hannink, Anne; Brandl, Beate; Skurk, Thomas; Hauner, Hans; Sieber, Cornel; Volkert, Dorothee (Frontiers in Aging, 2022)
Aging is associated with reduced appetite as well as a slight increase in pro-inflammatory status, which both might contribute to the development of malnutrition. We aimed to evaluate the association between inflammation based on serum C-reactive protein (CRP), and appetite in healthy community-dwelling older adults. In this cross-sectional study of 158 healthy and non-smoking persons (aged 75-85 years), appetite was assessed in personal interviews by a single question with five answer categories. As nobody reported (very) poor appetite, the remaining three categories were dichotomised into "(very) good" and "moderate" appetite. Fasting serum CRP was analysed according to standard procedures, values ≥ 5.0 mg/L were considered as inflammation. The association between inflammation and appetite was examined by binary logistic regression, unadjusted and adjusted for age, sex, waist circumference, leptin, depressive mood, number of medications, interleukin-6 and tumor necrosis factor-α. Appetite was very good in 27.8%, good in 58.9%, and moderate in 13.3% of participants. Inflammation was present in 10.8% overall, in 8.8% of those with (very) good and in 23.8% of those with moderate appetite (p = 0.038). In the unadjusted model, participants with inflammation were 3.2 times more likely to have moderate appetite (95%CI: 1.01-10.44, p = 0.047). In the adjusted model, the odds of having moderate appetite was 3.7 times higher in participants with inflammation, but no longer significant (95%CI: 0.77-18.55, p = 0.102). In healthy older people, we found hints for a potential association between increased levels of CRP and a slightly reduced appetite. More studies in larger samples are needed.
EVALuna2:505824

Does a 12-month transitional care model intervention by geriatric-experienced care professionals improve nutritional status of older patients after hospital discharge? A randomized controlled trial - Chareh, Neshat; Rappl, Anja; Rimmele, Martina; Wingenfeld, Klaus; Freiberger, Ellen; Sieber, Cornel; Volkert, Dorothee (Nutrients, 2021)
At hospital discharge, many older patients are at health and nutritional risk, indicating a requirement for ongoing care. We aim to evaluate the effects of comprehensive individualized care by geriatric-experienced care professionals, the so-called “pathfinders”, on nutritional status (NS) of older patients after discharge. A total of 244 patients (median age 81.0 years) without major cognitive impairment were randomized to intervention group (IG: 123) or control group (CG: 121) for a 12-month intervention, with up to 7 home visits and 11 phone calls. The comprehensive individualized care contained nutritional advice, when required. The intervention effect after three (T3m) and 12 (T12m) months on change in MNA-SF (Mini Nutritional Assessment-Short Form) and BMI was evaluated by Univariate General Linear Model (ANOVA), adjusted for age, sex, living situation, and activities of daily living. At baseline, mean MNA-SF did not differ between IG and CG (10.7 ± 2.6 vs. 11.2 ± 2.5, p = 0.148); however, mean BMI was significantly lower in IG compared to CG (27.2 ± 4.7 vs. 28.8 ± 4.8 kg/m2, p = 0.012). At T3m, mean change did not differ significantly between the groups, neither in MNA-SF (0.6; 95%CI: −0.1–1.3 vs. 0.4; −0.3–1.1, p = 0.708) nor in BMI (−0.2; −0.6–0.1 vs. 0.0; −0.4–0.4 kg/m2, p = 0.290). At T12m, mean change of MNA-SF was significantly higher in IG than in CG (1.4; 0.5–2.3 vs. 0.0; −0.9–0.8; p = 0.012). BMI remained unchanged in IG, whereas it slightly declined in CG (0.0; −0.7–0.6 vs. −0.9; −1.6– −0.2 kg/m2, p = 0.034). We observed rather small effects of comprehensive individualized care by pathfinders on NS in older patients 12 months after discharge. For more pronounced effects nutrition expertise might be needed.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Geriatric rehabilitation; Hospital discharge; Nutrition advice; Older adults; Transitional care

Does a 12-month Transitional Care Model (TCM) Intervention "Boy Scout" lead to an Improvement in the Nutritional Status of elderly Patients after Discharge from Hospital? A randomized controlled Study - Chareh, Neshat; Rappl, Anja; Rimmele, Martina; Wingenfeld, K.; Freiberger, Ellen; Sieber, Cornel; Volkert, Dorothee (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Nutritional care of home-cared older adults depends on type of care and living situation - Chareh, Neshat; Kiesswetter, Eva; Heseker, H.; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Type of Care and Living Situation Are Associated with Nutritional Care but Not Nutritional Status of Older Persons Receiving Home Care - Chareh, Neshat; Kiesswetter, Eva; Rappl, Anja; Stehle, Peter; Heseker, Helmut; Sieber, Cornel; Volkert, Dorothee (Healthcare, 2020)
Nutritional care and nutritional status may differ in older persons receiving informal (IC) or professional (PC) home care and further depend on the living situation, but little is known in this regard. In this analysis of a cross-sectional multicenter study, type of care, living situation, and nutritional care were enquired in 353 older adults (>= 65) receiving IC or PC, living either with partner (LP), with others (LO) or alone (LA), and the nutritional status was determined by BMI and MNA(R). For IC receivers, food shopping (IC-LP 94%, IC-LO 96%, IC-LA 92%) and warm meals (IC-LP 89%, IC-LO 90%, IC-LA 71%) were mainly provided by relatives, whereas 47% of PC-LA prepared warm meals by themselves and 22% received meals on wheels. Thirteen percent were underweight, 13% malnourished, and 57% at risk of malnutrition without differences between the groups. Adjusted odds ratios (OR) of being malnourished were also not different (IC-LP 2.2 [95% CI 0.5-9.7], IC-LO 1.4 [0.3-6.6], IC-LA 1.4 [0.3-6.6]) compared to PC-LA. In conclusion, provision of nutritional care obviously differed according to the type of care and living situation, whereas nutritional status does not seem to be affected by these aspects. More research is clearly needed in this field.
CRIS-Team WoS Importer:2020-11-06